DETECTION OF BACILLUS THURINGIENSIS CRYSTAL PROTEIN CRY51AA1 INTOXICATION (IN VIVO) USING ZEBRAFISH MODEL - Ali B.T. Aldeewan (Basrah Journal of Veterinary Research)
Bacillus thuringiensis is a ubiquitous a gram-positive, anaerobic, spore-forming bacterium, produces various proteins (toxins) during the stationary and vegetative phase of its growth cycle. Some of these proteins belonging to this group showed weak similarities to ß-barrel pore-forming toxic proteins, such as the cytotoxins of Pseudomonas aeruginosa, the epsilon toxin of Clostridium perfringens, alpha-toxin of Clostridium septicum. In the present study, the intoxication effects of Cry51Aa1 protein produced by B.thuringiensis F14-1 strain was evaluated in vivo, in order to investigate the ability of activated Cry51Aa1 to make a change in size or functions of zebrafish cardiovascular system and induces toxicity in adult zebrafish. Using in vivo imaging we observed that Cry51Aa1 has no scientific effect on cardiac function and development of zebra fish embryo or have toxic effect on adult in spite of use high concentration, so it is safe to use and a potentially effective agent in breast cancer therapy.